2022
DOI: 10.21203/rs.3.rs-2076134/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota-derived short-chain fatty acids promote prostate cancer progression through inducing cancer cell autophagy and M2 macrophage polarization

Abstract: Objective: Emerging research have reported the regulative role of gut microbiota-derived short-chain fatty acids (SCFAs) within tumor microenvironment. In previous study we have demonstrated abnormal gut microbial composition in castration-resistant prostate cancer (CRPC) patients, here we sought to reveal the mechanism of SCFAs as a mediator linking microbiota dysbiosis and prostate cancer (PCa) progression. Methods:By using transgenic TRAMP mouse model, PCa patient samples, in vitro PCa cell transwell assay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Recently, Liu et al [ 78 ] have observed the effect after transplantation of a fecal suspension from a patient with castration refractory prostate cancer (CRPC) into a transgenic TRAMP mouse model (unpublished). Fecal material transplantation from CRPC patients accelerated cancer progression in TRAMP mice.…”
Section: Short Chain Fatty Acidmentioning
confidence: 99%
“…Recently, Liu et al [ 78 ] have observed the effect after transplantation of a fecal suspension from a patient with castration refractory prostate cancer (CRPC) into a transgenic TRAMP mouse model (unpublished). Fecal material transplantation from CRPC patients accelerated cancer progression in TRAMP mice.…”
Section: Short Chain Fatty Acidmentioning
confidence: 99%
“…These findings suggest that SCFAs may play a role in PCa progression [ 67 ]. Liu et al [ 108 ] recently transplanted fecal suspension from a castration-refractory prostate cancer (CRPCa) patient into a transgenic adenocarcinoma of the mouse prostate (TRAMP) mouse model. This transplantation resulted in the acceleration of cancer progression in the TRAMP mouse.…”
Section: Microbiome-derived Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…This transplantation resulted in the acceleration of cancer progression in the TRAMP mouse. In this study, SCFAs increased in vitro migration and invasion of PCa cells [ 108 ].…”
Section: Microbiome-derived Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…[7][8][9] The development of tumors and the effectiveness of cancer treatments strongly correlate with this genetic heterogeneity. 10,11 Furthermore, detecting genetic variations using bulk mRNA sequencing is challenging due to the significant intertumoral heterogeneity. The limits of several analytical approaches that capture intertumoral heterogeneity continue to be a key obstacle to this strategy, despite the fact that discovering oncogenic drivers using it has led to significant therapeutic advancements for some tumor types, such as melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Individual tumor cells develop cell‐specific genomic alterations due to mutation and clonal‐selection dynamics during tumor formation 7–9 . The development of tumors and the effectiveness of cancer treatments strongly correlate with this genetic heterogeneity 10,11 …”
Section: Introductionmentioning
confidence: 99%